Some Properties of Cyclotic Graph - U. M. Prajapati; S. K. Singh (International Journal of Mathematics And its Applications, 2016)
In the present work we have introduced a new graph called Cyclotic graph G(n,k). We have given many examples of Cyclotic graph G(n,k). We have proved some results about connectedness, planarity, regularity and number of edges in Cyclotic graph. We have also proved that G(n,k) is not Eulerian graph and found some results which shows when G(n,k) is bipartite and Hamiltonian.